ENHANCING HIGHER EDUCATION THROUGH FLIPPED CLASSROOM PEDAGOGY: STRATEGIES, IMPLEMENTATION CHALLENGES, AND IMPACT ON STUDENT ENGAGEMENT AND LEARNING OUTCOMES - Jonzokova Sayyora Anvarovna (Galaxy International Interdisciplinary Research Journal, 2024)
This research explores the innovative approach of flipping the university classroom, where traditional notions of lecture and homework are reversed. The study delves into various strategies employed by educators to implement flipped classroom pedagogy at the university level, investigating the impact on student engagement and learning outcomes. Additionally, the research aims to identify and address the challenges associated with flipping the university classroom, offering insights into effective solutions and recommendations for educators seeking to adopt this transformative teaching methodology.